2009
DOI: 10.1177/0020764008093686
|View full text |Cite
|
Sign up to set email alerts
|

Social Relationships as a Decisive Factor in Recovering From Severe Mental Illness

Abstract: The results show that recovery processes are social processes in which social relationships play a key role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
154
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(173 citation statements)
references
References 17 publications
(11 reference statements)
12
154
1
6
Order By: Relevance
“…These findings correspond with recent findings in recovery research (Schön et al 2009) defining the social relationship aspect as the key experience related to other recovery factors. When the opportunity to talk through bad experiences here is seen as a core factor in mental health services, it is based on earlier surveys documenting the strong relationship between mental health and having someone to confide in (Strupp 1995, SSB 1998, Faktarapporten 2002.…”
Section: Sum Of Experiences That Helpedsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings correspond with recent findings in recovery research (Schön et al 2009) defining the social relationship aspect as the key experience related to other recovery factors. When the opportunity to talk through bad experiences here is seen as a core factor in mental health services, it is based on earlier surveys documenting the strong relationship between mental health and having someone to confide in (Strupp 1995, SSB 1998, Faktarapporten 2002.…”
Section: Sum Of Experiences That Helpedsupporting
confidence: 92%
“…This knowledge supports the suggestion that professionals should facilitate their clients' access to network resources (Granerud and Severinsson 2006). Additionally, as friendship programs have shown success in helping persons with severe mental illnesses (Wilson et al 1999, Hardiman 2004, Mccorkle 2009) and recent recovery research also emphasizes the essential importance of social relationships in the recovery process (Schön, Denhov, and Topor 2009), it is time to have a closer look at the quality of social networks compared to professional services and frankly discuss whether systems and services built on social support not only complement professional services, but also delineate a better course.…”
Section: The Roles Of Social Support and Professional Help In Relatiomentioning
confidence: 61%
“…In line with previous research (1,2,6,7,23) all participants perceived work to have a positive impact on daily life. On the other hand some participants perceived work to include conflicting experiences, which are findings that have not been presented before.…”
Section: Reclaiming the Worker Role 19supporting
confidence: 90%
“…Download date: 29. Aug. 2018 Introduction Work is at the heart of recovery for people with Severe Mental Illness (SMI) since it promotes both social relationships and social integration (1,2). The paradigm of recovery states that it is possible to recover in spite of a person having a SMI and that people with SMI can live independent and healthy lives, in contrast to the assumption of the condition being chronic (3).…”
mentioning
confidence: 99%
“…Sixty-seven percent of respondents in a study by Murray-Swank et al (2007) favored family participation in psychiatric treatment. Families often helped by lending money (Schon, Denhov, & Topor, 2009). Baxter and Diehl's (1998) study on recovery as a shared process between consumers and their families, identified advocacy as a primary activity of families who have learned to cope after the initial shock of diagnosis.…”
mentioning
confidence: 99%